Virtual Music Therapy: Developing New Approaches to Service Delivery. Issue 2 (8th September 2020) - Knott, David; Block, Seneca
Abstract: As the global Coronavirus disease (COVID-19) pandemic transforms our society, music therapists must adapt service delivery models that ensure client safety. Given the prevalence of COVID-19 in our communities and lack of personal protective equipment in many settings, music therapists are faced with the need to shift delivery models in order to provide safe and relevant services. Telehealth is one solution to these current service delivery challenges. Music therapists possess a depth of practice-based knowledge and understanding of client populations, which enables them to develop virtual services, matching both the clinicians' and clients' technical capabilities. Developed during the initial wave of COVID-19 infections in the United States, this article describes the coauthors' three-tiered scaffold model intended to support the program development and deployment of virtual music therapy (VMT) services. The model describes an approach to developing VMT services that directs the clinician's goals of care in formats that are accessible, appropriate, and best meet the patient/client's needs and abilities. The severity and lasting nature of this worldwide health crisis and its disruption of traditional service delivery models require clinicians and researchers to develop the most effective uses of VMT while considering its limits with regard to clinical populations and need areas.